2000
DOI: 10.1046/j.1471-4159.2000.0742041.x
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Glutamate in the Expression of Inducible Nitric Oxide Synthase After Oxygen and Glucose Deprivation in Rat Forebrain Slices

Abstract: Nitric oxide synthesis by inducible nitric oxide synthase (iNOS) has been postulated to contribute to ischemia-reperfusion neurotoxicity. The expression of this enzyme has been demonstrated in cells present in the postischemic brain. The mechanisms of iNOS expression after cerebral ischemia are a subject of current research. We therefore decided to investigate whether glutamate, which is released in ischemia and is implicated in neurotoxicity, might be involved in the mechanisms by which oxygen and glucose dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(34 citation statements)
references
References 62 publications
3
30
0
1
Order By: Relevance
“…Rats were decapitated, their hippocampi were quickly dissected out and transverse sections (400 lm) were rapidly obtained using a McIlwain tissue chopper. One slice was placed into each well of a 24-well culture plate and preincubated for 15 min in a modified Krebs-Henseleit solution at 37°C in an atmosphere of 5% CO 2 (95%O 2 / 5%CO 2 ) [33].…”
Section: Oxygen and Glucose Deprivation (Ogd) Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats were decapitated, their hippocampi were quickly dissected out and transverse sections (400 lm) were rapidly obtained using a McIlwain tissue chopper. One slice was placed into each well of a 24-well culture plate and preincubated for 15 min in a modified Krebs-Henseleit solution at 37°C in an atmosphere of 5% CO 2 (95%O 2 / 5%CO 2 ) [33].…”
Section: Oxygen and Glucose Deprivation (Ogd) Experimentsmentioning
confidence: 99%
“…Slices corresponding to the ''ischemic'' experimental group were incubated in a solution without glucose for 60 min in an anaerobic chamber, saturated with N 2 , with temperature kept at 37°C. After this period, the incubation solution was replaced with fresh control medium, and slices were incubated for 3 or 24 h at 378C in an atmosphere of 5% CO 2 (95%O 2 /5%CO 2 ) to simulate a ''reperfusion'' period [33]. Assessment of neural injury-LDH assay: Neural cell injury was quantified by the measurement of lactate dehydrogenase (LDH) released from damaged cells into the extracellular fluid.…”
Section: Oxygen and Glucose Deprivation (Ogd) Experimentsmentioning
confidence: 99%
“…NADPH oxidase (NOX), which catalyzes the generation of superoxide anions (O 2 - ∙), is one of the main contributors to excessive ROS in I/R injury [5,6]. Another important ROS generator is nitric oxide (NO) generated from inducible NO synthase (iNOS), which is induced in models of brain ischemia both in vitro and in vivo [7,8]. NO can react with O 2 - ∙ to produce peroxynitrite (ONOO - ), which is a strong oxidative radical that causes protein nitration and dysfunction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Excitotoxicity induced by activation of glutamate receptors is the predominant mechanism underlying neuronal apoptosis in stroke [4] . Cerebral ischemic damage is associated with excessive release of excitatory glutamate, which subsequently upregulates not only the expression of neuronal nitric oxide synthase (nNOS), but also inducible nitric oxide synthase (iNOS) [5,6] . Numerous studies [7][8][9][10] have shown that the glutamate receptor-postsynaptic density-95 (PSD-95)-nNOS complex and iNOS produce an excessive amount of nitric oxide (NO) during cerebral I/R injury; NO immediately reacts with superoxide radicals to form peroxynitrite, which subsequently nitrates protein tyrosine residues, generating nitrotyrosine and leading to oxidative/nitrative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Toxic NO-mediated oxidative/nitrative stress during cerebral I/R injury may contribute to the activation of the apoptotic cascade [11] . In vitro studies [5,12] have demonstrated that the NO-induced apoptotic signaling cascade involves mitogen-activated protein (MAP) kinase-mediated Bax translocation from the cytosol to the mitochondria and subsequent caspase-3 activation in cultured In previous studies, FA reduces cerebral ischemic injury by weakening the expression of PSD-95 in the ischemic area and provides neuroprotection against apoptosis partly via inhibiting intercellular adhesion molecule-1 (ICAM-1) mRNA expression in a transient middle cerebral artery occlusion (MCAo) model [13,14] . In addition, FA inhibits glutamate-induced apoptosis through modulation of the MAP kinase signaling pathway in cultured cortical neurons [15] .…”
Section: Introductionmentioning
confidence: 99%